STUDI KRITIS ATAS KONSEP NĀSIKH-MANSŪKH - Asmu'i Asmu'i (Universitas Darussalam Gontor, 2013)
The characteristic of the liberal view is anti-authority, even to the scholar muslims or to the revelation, and demanding Islamic Sharia to adapt to the modern human rights. The authorities in religion (ulema) disagreed with this way of thinking, because it contradicted to the Islamic Sharia. For the supporters of religious liberalism, religion must be reinterpreted and if possible must be deconstructed. One of the bearers of the idea is Abdullahi Ahmed An-Na’im, a Sudanese Muslim thinker. He considered thatsharia (jurisprudence) that have existed before and done is a factor of setbacks and backwardness of Muslims today. Sharia is not something sacred (divine), because it is not a direct revelation from God Almighty. Na’im deconstructed an Islamic Sharia through the renewal of Usul Fiqh which has been established in the teachings of Islam. In this regard, he specifically deconstructs the concept of naskh in Islam, and offers a newconcept which considered as the answer to the backwardness of Muslims.